(3EVGAI GdOLfI aj YbGFO Cgd GdSfIs - (3GdebQj GdeZQHj GdJdeSGfj GdaGSj GdeUQj, CHh GdYHGS, CMeO Hf eMeO Hf CMeO Hf jMji, (B1041 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; hHg KbJj (B- (3jbhd CMeO GdabjQ GdebQj GdeZQHj GdeGdcj GdCTYQj (B- (3GdMeO ddg GdPj JhMjOg CLd eG GYJfi Hg YHjOgs
(3BNQgG (B:s
(3cfR GdHQGjG GdgGTej GdYQHj efjdge eG CedhG ef CQH (B- (3Ydjg ef Bd hCUMGH YdhG bOQG hGJHGY HGMSGf JdhG (B- (3CRci JMjGJ hCSeG hCfJe jRchG HgG eHJOC heNJJes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 237s
(3eYLe GdeDdajf (B1 / 248s
(3EjVGM Gdecfhf (B1 / 94s
(3gOjI GdYGQajf (B1 / 157s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds